RADI-04. Stereotactic radiosurgery in alveolar soft part sarcoma brain metastasis. (9th August 2021) - Lim, Jia Xu; Karlsson, Bengt; Pang, Angela; Balamurugan, Vellayappan; Nga, Vincent
Abstract: Background: Alveolar soft part sarcoma (ASPS), although rare, has the highest incidence of brain metastasis amongst all sarcomas. Stereotactic radiosurgery (SRS) has been shown to be a well tolerated and effective treatment of intracranial sarcomatous metastasis. However, there is a paucity of published literature that guides radiation therapy in this condition. Methods: This is a single centre retrospective review of all ASPS patients with intraparenchymal brain metastasis in our centre treated with stereotactic radiosurgery (SRS). SRS dosing is dichotomised into high and low dose (≥25 Gy and <25 Gy respectively) and outcomes such as local recurrence (LR) and radiation effects are noted. Successful treatment was defined as a lesion that regressed, is stable, or has less than 25% increase in tumour volume. Local recurrence (LR) was defined as increase in tumour volume by more than 25% during follow up. Results: There were three patients with 11 ASPS metastatic brain lesions, one of which underwent retreatment. Each lesion was followed up for a mean duration of 12 months (range: 5 – 22 months). Five lesions treated with a high dose regime and six lesions were given low dose. Lesions treated with high dose SRS experienced significantly less LR (20% vs 83.3%, OR 20.0 [95%CI 0.93 – 430), p = 0.036) with no increase in undue symptomatic radiation effects. Retreatment of lesions with LR after initial SRS using a low dose regime was successful, albeit only in the single recurrent lesion. Conclusions: We conclude that SRS can be used as a first line treatment for ASPS brain metastasis that are not surgically accessible and that using a high dose for treatment is effective and safe. Multicentre collaborative studies can be performed to validate this claim.